SPECIALIST NURSING CARE AT ERADAH COMPLEX AND MENTAL HEALTH: IMPROVING MENTAL HEALTH SERVICES IN SAUDI ARABIA (Lex localis - Journal of Local Self-Government, 2024)
Mental health problems are one of the most significant contributors to the global burden of disease in developed and developing countries. They can result in a long-term health and social care burden, associated with increased hospitalization rates, outpatient clinic attendances, overall demand on emergency services, demand on diagnostic laboratory services, increased instances of unemployment, employment being hampered, neglect of other family members' needs, higher divorce rates, and ultimately death. The nursing management and prevention of physical health problems for patients suffering from other mental health issues are among the most crucial issues. The leadership and skills of specialized nurses are of utmost significance. A specialized mental health nurse can provide better physical skills, assess and monitor, develop treatment plans, collaborate with other health care professionals, provide complete and effective care, and assist patients in various ways.The need for specialist nurses for mental health and complex care is not advanced in Saudi Arabia, and the present specialist mental health nurses in the country are not highly skilled at addressing the needs of patients with mental health issues. In many of these facilities, there is a lack of specialized acute nursing staff focused on mental health. Instead, as needed, they take up the balance, without hospital ratios indicating too high a dependency on acute care and leaving core tasks undone. In general acute care conditions, the incorrect skills, attitudes, values, and level of understanding of the patient population of the specialized point-of-care staff render acute mental health care inadequate. The Saudi commission increased the qualification of general nurses to be 4-year bachelor's degrees in nursing, and the health authorities in the region are encouraging the graduation of registered nurses specializing in mental health.